Phonological Rules of Malay Kepulauan Local Language in Batam Island - Ambalegin, Ambalegin (Universitas Negeri Padang, 2024)
A local language may disappear due to some factors. Modernity and melting pot are able to shift the local language. Malay Kepulauan is the local language of Batam island, and it tends to be left. It needs to be documented. This qualitative research gathered information of Malay Kepulauan from the locals. The aim was to reveal the process of its articulation. The data were taken from some Kampong Tua: Nongsa, Sanggau, Tanjung Uma, Telok Air, and Tanjung Riau. Observational method included semi-structured interview and record. The data in term of sounds were transcribed phonemically to capture the process of deletion and insertion. The result of this research was that Malay experienced reciprocal assimilation, synchronic dissimilation, aphaeresis deletion, syncope deletion, apocope deletion, epenthesis insertion, neutralization, and metathesis. The phonemic environment of phonological rules is /b/, /p/, /t/, /d/, /k/, /Ɂ/, /m/, /n/, /Ɍ/, /z/, /ʝ/, /h/, /j/. /w/, and /l/. The vocalic sounds involved the alteration; /ʌ - ə/, /ʊ - ɒ/, /e - I/. The benefit of having assimilation, dissimilation, deletion, insertion, neutralization, and metathesis in pronouncing is resulting in smoother, more effortless, and more economical transition from one to another sound. However, phonological rules phenomena in Malay Kepulauan do not change the meaning of the words lexically